An Analysis of Gorontalo and Arabic Oral Literature: A Contrastive Review to Identify Poetry Types - A.Tjalau, Cutri; Awaliyah Adam, Ayu Cahya; Puteri Doni, Chaterina (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
Oral literature is a form of literary work that originates from ancient societies, which still prioritize traditional values to shape individual character through messages passed down through generations. This study uses a library research method, a research approach that examines and analyzes books, literature, journals, notes, and relevant reports as research sources related to the issue being studied. The purpose of this article is specifically to detail the similarities and differences in the types of oral poetry in Gorontalo and Arabic. The results of this study show that both Gorontalo and Arabic oral poetry have similarities and differences. The similarity lies in the function of the poetry, which serves as a means of communication to preserve and convey cultural values, history, and traditions from one generation to the next. As for the differences, Gorontalo oral poetry tends to emphasize the wisdom of customs and adherence to Islam, while the themes in Arabic oral poetry reflect the valor of the Arab people, in line with the tough character of the Arab nation. In addition, Gorontalo oral literature also includes Lumadu poetry, which offers entertainment through riddles, a feature not found in Arabic oral literature. In terms of presentation, Gorontalo oral poetry is delivered through songs or recitations accompanied by traditional music, while Arabic oral poetry relies more on verbal power and rhetoric without the use of musical instruments.